The Stability, Microstructure, and Microrheological Properties of Monascus Pigment Double Emulsions Stabilized by Polyglycerol Polyricinoleate and Soybean Protein Isolate - Xu, Duoxia; Zheng, Boyan; Che, Yixin; Liu, Guorong; Yuan, Yingmao; Wang, Shaojia; Cao, Yanping (Frontiers in Nutrition, 2020)
Monascus pigment is a natural food pigment and is commonly used for coloring and antiseptic of cured meat products, confectionery, cakes and beverages. However, Monascus pigment is sensitive to environmental conditions. The main aim of this study was to investigate the effect of polyglycerol polyricinoleate (PGPR) and soy protein isolate (SPI) on the particle size, zeta-potential, physical stability, microstructure and microrheological properties of Monascus pigment double emulsions. The effects of ionic strength, heating, and freeze thawing treatment on the stabilities of Monascus pigment double emulsions were also characterized. It was found that the optimum conditions for fabricating Monascus pigment double emulsion was 3.6 wt% PGPR and 3.0 wt% SPI. The fabricated Monascus pigment double emulsion was composed of fine particles with narrow and uniform size distributions. Microrheological property results suggested that the elastic characteristic of the Monascus pigment double emulsion was dorminated with increasing PGPR and SPI contents. It was mainly due to the increased collision and interaction between the droplets during the movement resulting in force increasing. Monascus pigment double emulsions with less than 5 mM CaCl2 prevented calcium to destroy the physical stability of emulsions. While, Monascus pigment double emulsions with more than 10 mM CaCl2 formed creaming. After freeze thawing treatment, creaming occurred in Monascus pigment double emulsion. However, it was stable against heating treatment due to heating leading to dense network structure. It could be contributed to the practical applications of Monascus pigment double emulsions in food products.